2017
DOI: 10.3847/1538-4357/aa6718
|View full text |Cite
|
Sign up to set email alerts
|

What Can We Learn about GRB from the Variability Timescale Related Correlations?

Abstract: Recently, two empirical correlations related to the minimum variability timescale (MTS) of the light curves are discovered in gamma-ray bursts (GRBs). One is the anti-correlation between MTS and Lorentz factor Γ, and the other is the anti-correlation between the MTS and gamma-ray luminosity L γ . Both of the two correlations might be used to explore the activity of the central engine of GRBs. In this paper, we try to understand these empirical correlations by combining two popular black hole central engine mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…As shown in Xie et al (2017), this model can hardly reproduce the observed MT S − L correlation. It is worth mentioning that they defined MT S as the viscous timescale due to the viscous instability.…”
Section: Discussionmentioning
confidence: 87%
“…As shown in Xie et al (2017), this model can hardly reproduce the observed MT S − L correlation. It is worth mentioning that they defined MT S as the viscous timescale due to the viscous instability.…”
Section: Discussionmentioning
confidence: 87%
“…Yi et al (2017b) compared the observational results with a positive correlation between Γ0 (the initial Lorentz factor) and the jet power from the two types of BH central engine models, i.e.,the ν ν -annihilation mechanism (non-magnetized model) and the Blandford & Znajek mechanism (hereafter BZ, a strongly magnetized model), and they found that some parameters are contrived for the ν ν -annihilation mechanism, whereas the latter (BZ) mechanism can generally account for the observations, which also can be seen in Lei et al (2013). The result is further confirmed by Xie et al (2017), and by using the empirical correlation between Lorentz factor and minimum variability timescale. If X-ray fares are indeed powered by the BZ mechanism of a hyper-accreting BH system, then what can we learn about the properties of GRB central engine from these X-ray flares data?…”
Section: Introductionmentioning
confidence: 75%
“…As discussed in Lei et al (2013), Xie et al (2017) and Yi et al (2017b), two parameters of prompt emission, i.e., the beaming corrected γ-ray luminosity Lγ and initial Lorentz factor Γ0, are highly related to the properties of GRB central engines, and thus used to study the properties of central objects. X-ray flares are believed to be generated by the late activities of central engine.…”
Section: Sample Selectionmentioning
confidence: 99%
“…The hyper-accreting BH system can launch a relativistic jet via neutrino-antineutrino annihilation (Popham et al 1999;Narayan et al 2001;Di Matteo et al 2002;Gu et al 2006;Chen & Beloborodov 2007;Janiuk et al 2004Janiuk et al , 2007Liu et al 2007Liu et al , 2015Lei et al 2009Lei et al , 2017Xie et al 2016), or Blandford-Znajek mechanism (hereafter BZ; (Blandford & Znajek 1977;Lee et al 2000;Li 2000;Lei et al 2005Lei et al , 2013). The neutrino annihilation mechanism suffers strong baryon loading from the disk and therefore may be too "dirty" to account for a GRB jet Xie et al 2017). For this reason, we suppose that the jet powering the X-ray bump is dominated by the BZ mechanism.…”
Section: The Modelmentioning
confidence: 99%